Protocol of a randomized controlled study of the PneumRx endobronchial coil system versus standard-of-care medical management in the treatment of subjects with severe emphysema (ELEVATE) - Herth, Felix (Respiration, 2019)
Background: The PneumRx endobronchial coil system for patients with severe emphysema has been shown to improve quality of life, exercise capacity, and pulmonary function in patients with emphysema. A post hoc analysis of the RENEW trial has identified patient characteristics and lobar selection methods associated with improved outcomes, which have to be confirmed prospectively. Methods: The ELEVATE trial is a prospective, multicenter, open label, randomized (2:1), controlled trial comparing outcomes in patients treated with endobronchial coils (treatment) to a medically managed control group (control). The trial aims to enroll 210 patients (140 in the treatment group and 70 in the control group) with severe emphysema. Control patients will be eligible to crossover to coil treatment after 6 months of follow-up. The co-primary effectiveness endpoints are percent change in forced expiratory volume in 1 s and quality of life measured by change in St. George’s Respiratory Questionnaire from baseline to 6 months. Secondary objectives are determination of responder rates of clinical endpoints and mean change in other functional and physiologic endpoints. All patients will be followed for 24 months after initial treatment. Adverse events will be collected on an ongoing basis throughout the trial. Discussion: The primary objective of the ELEVATE trial is to prospectively confirm the safety and effectiveness profile of the coil system for the treatment of severe emphysema in consideration of the findings of previous randomized controlled trials. Secondary objectives are the determination of responder rates in all clinical endpoints and mean change in physiologic endpoints.
Gesehen am 20.02.2020